2009
DOI: 10.1111/j.1423-0410.2009.01206.x
|View full text |Cite
|
Sign up to set email alerts
|

Prion removal effect of a specific affinity ligand introduced into the manufacturing process of the pharmaceutical quality solvent/detergent (S/D)‐treated plasma OctaplasLG®

Abstract: This new single-use, disposable PrP(Sc)-harvesting gel ensures a very high capacity in terms of removing the pathogenic agent causing vCJD from the new generation OctaplasLG, in the event that prions can be found in plasma from donors incubating the disease and thereby contaminating the raw material plasma used for manufacturing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
32
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 13 publications
(19 reference statements)
0
32
0
Order By: Relevance
“…Haemostatic variables and thrombin generation were compared with Octaplas, there was no significant difference between the products. Therefore, the addition of affinity chromatography does not appear to adversely affect the haemostatic quality [20,21].…”
mentioning
confidence: 94%
“…Haemostatic variables and thrombin generation were compared with Octaplas, there was no significant difference between the products. Therefore, the addition of affinity chromatography does not appear to adversely affect the haemostatic quality [20,21].…”
mentioning
confidence: 94%
“…Recently, Octapharma modified the manufacturing process for solvent detergenttreated FFP to incorporate a chromatographic step that selectively binds abnormal prion-related protein (PrP) to an affinity Ligand Gel (OctaplasLG, Octapharma, AG, Vienna, Austria). Using this procedure, Octapharma has demonstrated greater than or equal to 3.0 log reduction using scrapie models of abnormal prion protein [15]. OctaplasLG is licensed in Europe and has now replaced Octaplas.…”
Section: Pathogen Reduction Technologymentioning
confidence: 99%
“…A validated Western blot (WB) test was used for the identification and quantification of PrP Sc . After the implementation of the prion removal chromatography step into the Octaplas manufacturing process (2nd generation) a total RF of ≥3.0 log10 was demonstrated [9]. Within this study it was further shown that the resin has the ability to bind infectious prion from sources like human vCJD and sporadic CJD.…”
Section: The State Of the Art Of The Sd-ffp In Respect To Implementatmentioning
confidence: 94%
“…The prion binding capacity per milliliter ligand gel was investigated using both intermediates and the final Octaplas product spiked with 263K hamster brain-derived prion (PrP Sc )-containing fractions [9]. A validated Western blot (WB) test was used for the identification and quantification of PrP Sc .…”
Section: The State Of the Art Of The Sd-ffp In Respect To Implementatmentioning
confidence: 99%